The Influence of Collaborative Governance on Bridge Construction in Marinding Village - Erfina; Hariyanti Hamid; ika fitria; Siska Riana Rahmat (Universitas Muhammadiyah Jember Press, 2025)
Infrastructure development in rural areas often faces challenges such as limited funding, inadequate technical support, and a lack of stakeholder collaboration. This study aims to analyze the influence of collaborative governance on bridge construction in Marinding Village, Bajo Barat District, Luwu Regency. The research employed a quantitative approach, using data collected through observation, closed-ended Likert-scale questionnaires, and literature review. A sample of 92 respondents was selected using a random sampling technique, and data analysis was conducted using simple linear regression with the aid of SPSS version 25. The findings reveal that the application of collaborative governance principles falls into the